HBR guide to getting the mentoring you need (Harvard Business Review Press, 2014)
Whether you’re eyeing a specific leadership role, hoping to advance your skills, or simply looking to broaden your professional network, you need to find someone who can help. Wait for a senior manager to come looking for you—and you’ll probably be waiting forever